Use of drugs that act on the cytochrome P450 system in the elderly (Clinics, 2009)
OBJECTIVES: The objective of this study was to analyze medications that act on the cytochrome P450 (CYP450) enzymatic system and are used daily by non-institutionalized elderly individuals. METHODS: A cross-sectional population-based study of elderly individuals (>; 60 years old) was conducted. All continuously used medications with hepatic metabolism via CYP450 that are classified as substrates, inducers or inhibitors were considered. For the analysis, elderly individuals were stratified according to age groups, and hepatic metabolism activity due to daily alcohol consumption and smoking were considered. RESULTS: Elderly individuals (396 in total: 222 women and 174 men) between 60 and 95 years of age (mean: 72.1) were assessed. Use of drugs that act on CYP450 was identified in 61.6% of the subjects. Drug use was observed among 16.2% of the subjects: three drugs among 9.8% and four or more among 6.3% of the subjects. The metabolic activities of the drugs used were classified as substrates (58.8%), inhibitors (14.9%), and inducers (4.3%). The main drugs used were beta-blockers and statins (as substrates), proton pump inhibitors and fluoxetine (as inhibitors), and prednisone and carbamazepine (as inducers). CONCLUSIONS: The results demonstrate that the elderly use high levels of medications that act on CYP450, thereby increasing the risk of drug interactions in a group that is already vulnerable to adverse drug effects.